2020
DOI: 10.1112/topo.12149
|View full text |Cite
|
Sign up to set email alerts
|

Maximal contact and symplectic structures

Abstract: We study the relationship on Weinstein domains given by Weinstein cobordism. Our main result is that any finite collection of high‐dimensional Weinstein domains with the same topology is Weinstein subdomains of a ‘maximal’ Weinstein domain also with the same topology. As applications, we construct many new exotic Weinstein structures, for example, exotic cotangent bundles containing many closed regular Lagrangians that are formally Lagrangian isotopic but not Hamiltonian isotopic and a new exotic Weinstein str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…That is, Stein fillable contact manifolds admit symplectic caps. For general higher-dimensional contact manifolds, it was not known until very recently that they admit (strong) symplectic caps [6,23]. This fact can be used to recover Theorem A (with the word "weakly" replaced by "strongly") from Theorem B, but our proof is independent of the existence of caps.…”
Section: Introductionmentioning
confidence: 88%
“…That is, Stein fillable contact manifolds admit symplectic caps. For general higher-dimensional contact manifolds, it was not known until very recently that they admit (strong) symplectic caps [6,23]. This fact can be used to recover Theorem A (with the word "weakly" replaced by "strongly") from Theorem B, but our proof is independent of the existence of caps.…”
Section: Introductionmentioning
confidence: 88%
“…Remark While completing a draft of this note, Oleg Lazarev sent a draft of his paper [21] in which he establishes Theorem 1.1 for almost‐Weinstein fillable contact manifolds (M2n1,ξ), using isotropic surgery of arbitrary index and coisotropic surgery of index n.…”
Section: Introductionmentioning
confidence: 99%
“…Remark While completing a draft of this note the authors learned that Oleg Lazarev had also obtained Theorem 1.6, see [21]. In addition, he showed that the partial order on contact manifolds coming from Weinstein cobordisms in dimensions above 3 has upper bounds for finite sets.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Weinstein cobordism, there are geometric constructions of a contact manifold Y that is Weinstein cobordant both from Y 1 and Y 2 given that there are Weinstein cobordism from Y to Y 1 , Y 2 in dimension ≥ 5 [49]. However it is not clear if such construction would yield something larger in Con ≤ or Con ≤,W .…”
mentioning
confidence: 99%
“…On the other hand, when we consider strong cobordisms, there are a lot more morphisms. In particular, if we include ∅ into the discussion, the existence of symplectic cap [25,49] implies that anything with a strong filling is equivalent to ∅ in Con ≤,S . Even if we throw out ∅ and even restrict to the case of connected strong cobordisms, the existence of strong cobordism is much less rigid compared to the the counterparts for exact or Weinstein cobordisms by [74].…”
mentioning
confidence: 99%